KOTA PELABUHAN AMBON 1817-1865:STUDI TENTANG PERKEMBANGAN Port of Ambon from 1817-1865:a Study of The Portdevelopment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
This thesis is focused on the evolution of the port city, Ambon, from 1817 to 1865. This period is based on the reason that 1817 was the Dutch recolonialization in Ambon. In the same year, a system of administration was established, named Gouvernernent der Molukken and the government was centralized in Ambon. The limitation of the year, 1865, is based on the reason that in 1865 there was a separation of system i.e., Manado became a residency, and so did Ternate. More over, three regencies - the central Maluku, Southeast Maluku and Southwest Maluku - were integrated and named Residentie Amboina that was centralized in Ambon. In the 1864, the Dutch left out the clove monopoly but the government would still accept clove from the inhabitants up to 1865. In the period of 1817 to 1865, the port of Ambon was declining as the result of political and economic domination of the Dutch, no free trade, the decline of the clove price in the European market, the condition of waters around the island of Ambon, the coastal condition of the port of Ambon, and the limited economic potencies of the island and the surrounding islands. The effect of the decline of the port city was the decline of the socio-economic sector.